Green Wall System to Reduce Particulate Matter in Livestock Housing: Case Study of a Dairy Barn - Alice Finocchiaro; Serena Vitaliano; Grazia Cinardi; Provvidenza Rita D’Urso; Stefano Cascone; Claudia Arcidiacono (Buildings)
Livestock farming has been identified as a significant contributor to atmospheric pollution, underscoring the necessity for the design and management of housing systems to adopt mitigation strategies. In the context of civil engineering, green wall systems are proving to be effective solutions for air filtration and purification. Nevertheless, research related to their application in livestock buildings is limited. This study focuses on the design, implementation, and performance evaluation of a modular, mobile green wall system that has been specifically developed to test PM2.5 concentrations’ reduction in naturally ventilated, free-stall dairy barns in the Mediterranean region. To this end, PM2.5 concentrations and climatic parameters have been measured before and after the application of the green wall system. Based on one-way analysis of variance, PM2.5 concentrations after the application were significantly lower (p < 0.001) than those before the mitigation strategy. The results of this study showed that the overall efficacy of the green wall reached 44%. The implementation of green wall systems offers a promising strategy to improve air quality in livestock facilities and to design aesthetically pleasing barns with a positive impact on the surrounding landscape.